2014
DOI: 10.1080/1747423x.2014.947642
|View full text |Cite
|
Sign up to set email alerts
|

Spatial information in ecosystem service assessment: data applicability in the cascade model context

Abstract: Spatial information and geographical information systems (GISs) are widely used in ecosystem service research, but both the information and the methods need to be properly understood in order to make coherent analyses. We discuss the practical challenges of incorporating spatial data to ecosystem service assessment in an agricultural landscape and apply the ecosystem service cascade model to put different data into context. We review the prerequisites and practices for successful 'ecosystem service GIS' and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It is unknown, however, whether these results can be generalized. For ES assessments to be useful for planning and management objectives they need to be conducted at relevant spatial scales, which frequently correspond to administrative levels, as those facilitate policy implementation (Tolvanen et al, 2014). The UN Strategic Plan for Biodiversity 2011-2020 urges subnational administrations to consider the development of biodiversity strategies to achieve the targets on biodiversity conservation, including the provision of ES (Aichi goal D, CBD, 2011-2020.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown, however, whether these results can be generalized. For ES assessments to be useful for planning and management objectives they need to be conducted at relevant spatial scales, which frequently correspond to administrative levels, as those facilitate policy implementation (Tolvanen et al, 2014). The UN Strategic Plan for Biodiversity 2011-2020 urges subnational administrations to consider the development of biodiversity strategies to achieve the targets on biodiversity conservation, including the provision of ES (Aichi goal D, CBD, 2011-2020.…”
Section: Introductionmentioning
confidence: 99%
“…The Intergovernmental Platform of Biodiversity and Ecosystem Services -IPBES -(UNEP, 2014; Díaz et al, 2015) has highlighted the advantages of frameworks as tools which simplify thinking, structure work, clarify issues, and provide a common reference point. Moreover, the EU-funded OpenNESS Project found that the cascade model has been used as an organizing framework (Pagella and Sinclair, 2014;Tolvanen et al, 2016), a tool for reframing perspectives (Spangenberg et al, 2014a,b;Brink et al, 2016), an analytical template (Boulton et al, 2016;Guisado-Pintado et al, 2016), and as an application framework (Chapman, 2014;Daw et al, 2016;Gissi et al, 2016).…”
Section: The Economic Demand Function (Edf)mentioning
confidence: 99%
“…The work by Tolvanen et al (2016) and Pagella and Sinclair (2014) illustrate how the cascade can be employed as an organising structure to help clarify ‘complex relationships’. The focus can be procedural as well as structural.…”
Section: The Role Of Conceptual Framework and The Cascade Modelmentioning
confidence: 99%
“…The focus can be procedural as well as structural. Tolvanen et al (2016) use the cascade to characterize the availability and applicability of spatial data for the analysis of an agricultural landscape, while Pagella and Sinclair (2014) use it to review different types of mapping tools. Both examples illustrate procedural types of usage.…”
Section: The Role Of Conceptual Framework and The Cascade Modelmentioning
confidence: 99%